Characterization of microsatellite markers in two exploited african trees, Entandrophragma candollei and E. utile (Meliaceae) - Monthe, F.S.; Duminil, J.; Tosso, F.; Migliore, J.; Hardy, Olivier J. (Wiley, 2017)
Premise of the study: Multiplexes of nuclear microsatellite primers were developed to investigate population genetic structure and diversity in two exploited African rainforest trees: Entandrophragma candollei and E. utile (Meliaceae). Methods and Results: Microsatellite isolation was performed simultaneously on two nonenriched genomic libraries after next-generation sequencing. We developed 16 and 22 polymorphic markers for E. candollei and E. utile in three and four multiplexes, respectively. The number of alleles ranged from two to 17 for E. candollei and from three to 19 for E. utile. Mean expected and observed heterozygosity ranged between 0.75 ± 0.13 and 0.55 ± 0.23 for E. candollei and between 0.73 ± 0.10 and 0.49 ± 0.2 for E. utile. Conclusions: These sets of nuclear microsatellite markers constitute useful tools for exploring gene flow patterns in these two Entandrophragma species.